Analisa Ekonomi Usaha Ternak Itik Pedaging di Kabupaten Langkat - Muhammad Buhari Sibuea (Jurnal Riset Agribisnis dan Peternakan, 2016)
The research was conducted in Pematang Cengal Barat Village, Tanjung Pura Subdistrict, Langkat Regency with the aim of identifying and knowing the availability of production inputs, business management systems, the amount of business income, and the contribution of broiler duck business income to overall income who also works as a rice farmer. The research area was determined purposively considering the unique characteristics of this business and the entire population of 30 people was used as the research sample. The data obtained were analyzed descriptively. From the research results, it is found that proportionally the availability of inputs or production factors for this business is quite good. Meanwhile, the broiler duck business management system is still carried out in a simple and traditional manner but has shown quite good results. The income received by broiler duck breeders is quite high in the season and it turns out that the contribution of the broiler duck business to the total income of the farmers is actually greater than their main business from lowland rice farming, which is 59.03%. The results of the research recommend that farmers who are also breeders make this business the main business whose maintenance can be carried out extensively and intensively so that it can produce better productivity.